Anti-Inflammatory Effect of Piper attenuatum Methanol Extract in LPS-Stimulated Inflammatory Responses. (25th July 2017) - Kim, You Jin; Deok, Jeong; Kim, Sunggyu; Yoon, Deok Hyo; Sung, Gi-Ho; Aravinthan, Adithan; Lee, Seungihm; Lee, Mi-nam; Hong, Suntaek; Kim, Jong-Hoon; Son, Young-Jin; Cho, Jae Youl
Abstract : Piper attenuatum is used as a traditional medicinal plant in India. One of the substances in P. attenuatum has been suggested to have anti-inflammatory effects. However, there is insufficient research about the anti-inflammatory mechanisms of action of P. attenuatum . The effects of P. attenuatum methanol extract (Pa-ME) on the production of inflammatory mediators nitric oxide (NO) and prostaglandin E2 (PGE2 ), the expression of proinflammatory genes, the translocation level of transcription factors, and intracellular signaling activities were investigated using macrophages. Pa-ME suppressed the production of NO and PGE2 in lipopolysaccharide- (LPS-), pam3CSK4-, and poly(I:C)-stimulated RAW264.7 cells without displaying cytotoxicity. The mRNA expression levels of inducible NO synthase (iNOS) and cyclooxygenase 2 (COX-2) were decreased by Pa-ME. P-ME reduced the translocation of p50/NF- κ B and AP-1 (c-Jun and c-Fos), as well as the activity of their upstream enzymes Src, Syk, and TAK1. Immunoprecipitation analysis showed failure of binding between their substrates, phospho- (p-) p85 and p-MKK3/6. p-p85 and p-MKK3/6, which were induced by overexpression of Src, Syk, and TAK1, were also reduced by Pa-ME. Therefore, these results suggest that Pa-ME exerts its anti-inflammatory effects by targeting Src and Syk in the NF- κ B signaling pathway and TAK1 in the AP-1 signaling pathway.